Financial Development, Cycles and Income Inequality in a Model with Good and Bad Projects - Spiros Bougheas; Pasquale Commendatore; Laura Gardini; Ingrid Kubin (Center for Economic Studies and ifo Institute (CESifo), 2022)
We introduce a banking sector and heterogeneous agents in the Matsuyama et al. (2016) dynamic over-lapping generations neoclassical model with good and bad projects. The model captures the benefits and costs of an advanced banking system which can facilitate economic development when allocates resources to productive activities but can also hamper progress when invests in projects that do not contribute to capital formation. When the economy achieves higher stages of development it becomes prone to cycles. We show how the disparity of incomes across agents de-pends on changes in both the prices of the factors of production and the reallocation of agents across occupations.
Keywords: E32; E44; G21; 330; banks; financial innovation; economic development; business cycles; income inequality